ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA (Studi Kasus : Perusahaan Food and Beverages yang Terdaftar di Bursa Efek Indonesia periode 2009 sampai dengan 2013) - Sari, Linda Purnama; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2015)
Profit growth is the ratio that showed how ability of company increased net profit over the previous year. The higher the ratio of profit growth, more better the company financial performance. This research wants to examine the effects of Current ratio, Debt to Asset ratio, total asset turnover,and net profit margin to profit growth of food and beverages company.The sampling technique used in this research is purposive sampling. There are 15 companies that used during the research. Analytical technique used in this research is multiple regression analysis by using SPSS 20. Data sample has tested using withÂ the classical assumption test such as normality test, multicollinearity, autocorrelation, and heteroskedasticity test. And the hypothesis test is done by using the F test, T test, and RÂ².The result of this research shows that current ratio, debt to asset ratio, total asset turnover, and net profit margin simultaneously have a significant influenceÂ to the profit growth of food and beverages company with a significance level of 0,000. From the research also known that partially Debt to Asset Ratio (DAR), Total Asset Turnover (TAT), and Net profit margin (NPM), have an influence a positive significant to profit growth of food and beverages company, while Current Ratio(CR) does not have positive significant influence to profit growth of food and beverages company.The value of adjusted R square is 29.3%. This means that 29.3% of profit growth can be explained by independent variable (Current ratio, debt to asset ratio, total asset turnover and net profit margin). While the remaining (70,7%) is explained by other variables or other causes.